The history of the democratic Russia movement in the Nizhny Novgorod region: political defeat was logical - A. A. Fomenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the history of the functioning of the movement «Democratic Russia» and, first of all, the Nizhny Novgorod branch of this structure. The aim of the work is to identify the features of the political activity of the movement «Democratic Russia» in 1990–1992 in the Nizhny Novgorod region. The tasks of the work are related to the identification of the most significant Nizhny Novgorod representatives of the movement, as well as the causes of splits in the organization. It is revealed that the reasons for the weakening and extinction of the movement «Democratic Russia» are almost the same both in the center and at the regional level.